Fluidnost identitete v dramatiki Matjaža Zupančiča - Pezdirc-Bartol, Mateja (Jezik in slovstvo, 2016)
In the dramatic work of Matjaž Zupančič, the question of identity takes centre stage, as is already evident in his dramatic debut The Exorcists (Izganjalci hudiča), first published in 1989, as well as in his most recent work, The Passage (Prehod), from 2015. Matjaž Zupančič is interested in the contradictions of the modern world, extreme situations provoked by the question of human identity. He is not, however, interested in cultural or national identities, but rather in the individual in his/her relationship with the collective and/or system.
Keywords: Zupančič, Matjaž, 1959-; Slovene literature; slovenska književnost; slovenska dramatika; slovenski dramatiki; slovensko gledališče; 21.st.; communication medium; mediji; identiteta; družba; society